Prinsip Keadilan Terhadap Pengecualian Bagi Pelaku Tindak Pidana Yang Diancam Pidana Di Bawah 5 Tahun - M. Arief Amrullah; Ainul Azizah; Yougha Aulia Mahardi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The existence of limitations on criminal penalties of more than 5 years and incapacity in Article 56 paragraph (1) of the Criminal Procedure Code means that those who commit crimes with a penalty of less than 5 years are no longer required to be provided with legal advice. The objectives of this research are limiting the defense of assistance to perpetrators of criminal acts under 5 years in accordance with the criminal justice system, providing assistance to perpetrators who are under 5 years under the principle of justice, reformulating the provision of legal assistance for perpetrators under 5 years. in the future. This research uses doctrinal legal research methods. The method used is to study and analyze legal materials and legal issues related to legal developments and problems. Legal aid is everyone's human right, which is not only provided by the state and not as a mercy from the state, but is the state's responsibility in realizing equality before the law, access to justice, and fair trials. The provision of legal assistance only looks at the criteria that the person is an incapacitated person who has met the requirements. limitations or limitations but it is an obligation for the state which must provide legal assistance to all Indonesian people without exception.